2018
DOI: 10.1177/0741932517751055
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Evidence-Based Practice Review on Teaching Mathematics to Students With Moderate and Severe Developmental Disabilities

Abstract: The purpose of this review was to examine the body of research on teaching mathematics to students with moderate and severe developmental disability that has been published since 2005, reflecting changes in both the academic expectations for this population and research and design standards in the evidence-based practice (EBP) era. We examined research on teaching mathematical skills for students with moderate and severe developmental disability from 2005–2016 and found 36 studies (33 single-case and three gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
148
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(157 citation statements)
references
References 37 publications
6
148
1
2
Order By: Relevance
“…Research also suggests that teaching students with IEPs who receive special education services requires unique skills. Broadly, our review identifies the importance of explicit and direct instruction (Powell & Fuchs, 2015;Spooner et al, 2019;Witzel, Mercer, & Miller, 2003), although evidence-based best practices can depend in part on the specific disabilities that students have (Schalock et al, 2010). For students with specific learning disabilitieswho make up the largest share of students with IEPs in our sample and in the U.S. population more broadly (U.S. Department of Education, 2018)-repeated reading can be effective (Ellis & Graves, 1990;Wexler, Vaughn, Roberts, & Denton, 2010).…”
Section: Teaching To Targeted Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research also suggests that teaching students with IEPs who receive special education services requires unique skills. Broadly, our review identifies the importance of explicit and direct instruction (Powell & Fuchs, 2015;Spooner et al, 2019;Witzel, Mercer, & Miller, 2003), although evidence-based best practices can depend in part on the specific disabilities that students have (Schalock et al, 2010). For students with specific learning disabilitieswho make up the largest share of students with IEPs in our sample and in the U.S. population more broadly (U.S. Department of Education, 2018)-repeated reading can be effective (Ellis & Graves, 1990;Wexler, Vaughn, Roberts, & Denton, 2010).…”
Section: Teaching To Targeted Populationsmentioning
confidence: 99%
“…instructional paradigms for general education students, particularly in mathematics, tend to emphasize constructivist perspectives and conceptually based teaching (Brophy, 2002;Cobb, 1994;Confrey & Kazak, 2006), views on instruction for students identified as ELs and those with IEPs are more mixed. Some emphasize the importance of conceptually based activities aligned to constructivism (Faggella-Luby, Griffith, Silva, & Weinburgh, 2016;Huerta, Tong, Irby, & Lara-Alecio, 2016), while others advocate for teaching grounded in direct instruction that uses explicit language and instructional techniques in order to maximize understanding of the content among ELs and students with IEPs (Doabler, Nelson, & Clarke, 2016;Spooner, Root, Saunders, & Browder, 2019).…”
mentioning
confidence: 99%
“…A large body of research has investigated the best practices and teaching strategies that might best serve a student population that includes students with mild to severe learning disabilities in mathematics (Spooner, Root, Saunders, & Browder, 2019). For example, in their comprehensive review of the literature on best practices for teaching mathematics to students with learning disabilities, Spooner et al (2019) concluded that systematic instruction, technology-aided instruction, and explicit instruction are considered evidence-based practices that best serve a population of students with learning disabilities in mathematics. Similarly, Jimenez and Stanger (2017) identified the use of virtual manipulatives as an evidence-based strategy that best serves students with disabilities.…”
mentioning
confidence: 99%
“…In general, they examine essential and desirable characteristics consisting of such components as the conceptualization of the study, participants and sampling, outcome measures, and data analysis. As group design research is not frequently used in work with students with severe disabilities, a detailed explanation of how these quality indicator criteria are applied has been omitted.In the area of severe disabilities, work has been done to respond to the mandates of NCLB, and has focused in particular on investigating and validating practices to teach academic skills to this population (literacy/language arts, Browder, Ahlgrim-Delzell, Spooner, Mims, & Baker, 2009;Browder, Wakeman, Spooner, Ahlgrim-Delzell, & Algozzine, 2006; mathematics, Browder, Spooner, Ahlgrim-Delzell, Harris, & Wakeman, 2008;Spooner, Root, Browder, & Saunders, 2016; science, Spooner, Knight, Browder, Jimenez, & DiBiase, 2011). In general, the Horner et al (2005) and Gersten et al (2005) quality indicator criteria were used with guidelines as to how to apply these criteria developed by the National Secondary Transition Technical Assistance Center (NSTTAC; Test et al, 2009) and the National Technical Assistance Center on Transition (NTACT; Test et al, 2015).…”
mentioning
confidence: 99%
“…Teaching students skills in mathematics represents the second most published literature for students with severe disabilities. In one of the first reviews on teaching mathematics to students with severe disabilities, Browder et al (2008) Browder et al (2008) found that most published studies taught skills within the National Council of Teachers of Mathematics (NCTM; 2000) numbers and operations and measurement standards, and the literature provided strong support for providing instruction on mathematical skills within in vivo settings.In an updated meta-analysis of research on teaching mathematical skills to students with severe disabilities, Spooner et al (2016) analyzed 36 total studies (33 SCD and three group experimental studies) published between January 2005 and August 2016. Of those 36 studies, 24 (22 SCD and two group studies) were evaluated to be of high or adequate quality, and were retained for analysis.…”
mentioning
confidence: 99%